Plz solve this both questions
Attachments:
![](https://hi-static.z-dn.net/files/db7/471bf8e4d064375cf05a32b70b45434c.jpg)
Answers
Answered by
1
Step-by-step explanation:
a) root6 x^2 - 4x-2root6=0
= root6x^2 - 6x + 2x - 2root6=0
= root6 x(x- root6) + 2(x- root6)=0
= (root6 x + 2)(x-root6) = 0
root6 x = -2 , x= root6
x=-2/root6 , root 6
b) ( x/x-3)^1/2 + (x-3/x)^1/2 = 5/2
let (x/x-3)^1/2 = y and (x-3/x)^1/2 = 1/y
y+1/y = 5/2 , y^2 + 1 =5/2y
now you can easily solve
pls mark as brainliest answer
Similar questions
Science,
5 months ago
Science,
11 months ago
Math,
1 year ago
Psychology,
1 year ago
Math,
1 year ago